Inhibition of α7-containing nicotinic ACh receptors by muscarinic M(1) ACh receptors in rat hippocampal CA1 interneurones in slices - Shen, Jian-xin (Blackwell Science Inc, 2009)
Cys-loop ligand-gated nicotinic ACh receptors (nAChRs) and G protein-coupled muscarinic ACh receptors (mAChRs) are expressed on rat hippocampal interneurones where they can regulate excitability, synaptic communication and cognitive function. Even though both nAChRs and mAChRs appear to co-localize to the same interneurones, it is not clear whether there is crosstalk between them. We utilized patch-clamp techniques to investigate this issue in rat hippocampal CA1 interneurones in slices under conditions where synaptic transmission was blocked. The α7 nAChR-mediated currents were activated by choline, and when the activation of this receptor was preceded by the activation of the M(1) mAChR subtype, the amplitude of α7 responses was significantly reduced in a rapidly reversible and voltage-independent manner, without any change in the kinetics of responses. This M(1) mAChR-mediated inhibition of α7 nAChRs was through a PLC-, calcium- and PKC-dependent signal transduction cascade. These data show that M(1) mAChRs and α7 nAChRs are functionally co-localized on individual rat hippocampal interneurones where the activation of these particular mAChRs inhibits α7 nAChR function. This information will help to understand how these cholinergic receptor systems might be regulating neuronal excitability in the hippocampus in a manner that has relevance for synaptic plasticity and cognition.